Associations between the Epithelial-Mesenchymal Transition Phenotypes of Circulating Tumor Cells and the Clinicopathological Features of Patients with Colorectal Cancer - Wu, Fengjie; Zhu, Jun; Mao, Yongjiang; Li, Xiaomei; Hu, Baoguang; Zhang, Dianliang (Disease Markers, 2017)
In this study, we identified CTCs using the previously reported CanPatrol CTC enrichment technique from peripheral blood samples of 126 patients with colorectal cancer (CRC) and found that CTCs could be classified into three subpopulations based on expression of epithelial cell adhesion molecule (EpCAM) (E-CTCs), the mesenchymal cell marker vimentin (M-CTCs), or both EpCAM and vimentin (biphenotypic E/M-CTCs). Circulating tumor microemboli (CTMs) were also identified in peripheral blood samples. Meanwhile, E-CTCs, M-CTCs, E/M-CTCs, and CTMs were detected in 76.98%, 42.06%, 56.35%, and 36.51% of the 126 patients, respectively. Interestingly, the presence of CTMs and each CTC subpopulation was significantly associated with blood lymphocyte counts and tumor-node-metastasis stage (P<0.001). Lymphocyte counts and the neutrophil-to-lymphocyte ratio (NLR) in patients lacking CTCs were significantly different from those in patients testing positive for CTMs and each CTC subpopulation (P<0.001). Our results indicate that tumor metastasis is more significantly associated with the presence of CTMs and M-CTCs than with other CTC subpopulations and suggest that EMT may be involved in CTC evasion of lymphocyte-mediated clearance.